Retroperitoneal ganglioneuroma with intraspinal growth - Benedek, Pedro; Crestanello, Francisco; Nin Vivo, Esteban; Purriel, Juan; Estable, Miguel; Grillo, Bartolomé (Cirugía del Uruguay, 1979)
The authors present a case of retroperitoneal neurocitoma (ganglioneuroma) with intraspinal growth througb tbe intervertebral foramina of L2 and L3, excised in three successive operations: an anterior transperitoneal approacb, a lateral_ Iumbotomy with resection of tbe lateral masses of tbe vertebrae L2 and L3 ( after Seddon) and a laminectomy. The patient is clinically cured with a follow - up of 42 months.